Preliminary survey on some detoxication/toxication enzymes in fishes from the Muda area - Surif, Salmijah; Heng, Phaik Heok; Nioi, Jelin; Arshad, Juzu Hayati (Malaysian Institute for Nuclear Technology Research, 1998)
Xenobiotic metabolising enzymes, specifically the mixed function oxidase (mfo), UDP-glucuronyl transferase (UDP-GT) and glutathione S?transferase (GST) in fishes have been used in this study as indicators of pesticide pollution in the ricefields. Activities of these enzymes were assayed in four fish species namely snakehead or haruan (Channa striata), climbing perch or puyu (Anabas testudineus), snakeskin gouramy or sepat siam (Trichogasterpectoralis) and walking catfish or keli (Clarias spp.) taken from six different locations within the Muda Irrigation Scheme on two different occasions. These areas are namely ACRBD4, Alor Gunung, Tanah Merah, Block 14, Sungai Sala in Kedah and Kampung Jelempok in Arau, Perlis. The last site, which practises biological and nonchemical pest control methods was taken as the control plot. Results from this study show no significant difference between the GST levels in Channa striata and Anabas testudineus taken from areas where pesticides are routinely used and that of the control area, suggesting that the level of pollution is not significant enough to cause elevated GST levels in these fishes. It was also interesting to note that there were species related differences in the levels of this enzyme in fishes from the same sites. The UDP-GT activities were higher in fishes exposed to pesticides compared to control fish. Esterase however appeared to be repressed in fishes from areas in which pesticides are freely used. Due to inconsistent number of catches at the two sampling times, these initial observations need to be treated with caution until substantiated with more samples and replicates in the future.